Investigation of factors affecting condensation on soiled PV modules. (1st January 2018) - Figgis, Benjamin; Nouviaire, Armelle; Wubulikasimu, Yiming; Javed, Wasim; Guo, Bing; Ait-Mokhtar, Abdelkarim; Belarbi, Rafik; Ahzi, Said; Rémond, Yves; Ennaoui, Ahmed
Graphical abstract: Highlights: Moisture adsorption by soiled surfaces studied by microscopy and isotherms. Microscopic condensation found on soiled surfaces well above the dew point. Hygroscopic material other than NaCl governed water uptake. Hydrophobic surface inhibited but did not eliminate condensation. Dust on PV modules in Qatar adsorbs much moisture when RH reaches 60–70%. Abstract: Condensation contributes to soiling of photovoltaic modules by trapping dust particles and, in certain conditions, leaving a material bridge between particles and the surface after evaporating. This study investigated the effects of four parameters on condensation on soiled surfaces: (i) relative humidity (RH), (ii) surface–dew point temperature difference, (iii) hygroscopic dust content, and (iv) surface wettability. Natural and synthetic dust mixtures of various compositions were studied via water adsorption isotherms, XRD, ion chromatography and optical microscopy, on hydrophilic and hydrophobic surfaces, in the lab and field. It was found that water uptake by surface dust was strongly dependent on its content of hygroscopic material, and such material allowed microscopic condensation droplets to exist on a soiled glass coupon even when it was significantly warmer than the dew point. A hydrophobic PTFE surface did not greatly retard the onset of condensation, compared to a glass surface, but did inhibit its growth. The implications for anti-soiling coatings are that it would be a difficult goal to eliminate condensation, and their performance will be influenced by dust composition and factors affecting condensation run-off such as RH and tilt angle. Variation in such parameters may partly explain inconsistent results from coating field trials reported so far.